The Effect of Academic Freedoms in Enhancing the Social Responsibility of Palestinian University Staff in the Gaza Governorates - Amal A. Al Hila; Mazen J. Al Shobaki; Samy S. Abu Naser (International Journal of Engineering and Information Systems (IJEAIS), 2017)
The research aims to demonstrate the effect of academic freedom in the promotion of social responsibility from the standpoint of teaching faculty members in Palestinian university of Gaza provinces. The researchers used descriptive analytical approach. The research community consists of the faculty members of (the Islamic University, Al-Azhar University, University of Palestine, University of Gaza, and University of Al-Aqsa), and the study tool is a questionnaire applied on a stratified random sample of staff members, and (250) questionnaires were obtained with recovery rate of (84.75%). The results of the study showed a statistically significant relationship between academic freedom in all its dimensions (teaching, expression of opinion, scientific research, decision-making, community service) and the promotion of social responsibility dimensions (administrative and procedural, societal, ethical and moral, environmental health, national and affiliation, cognitive and educational ) from the perspective of university teaching staff. Also it showed the presence of a statistically significant effect between academic freedoms (freedom of teaching, scientific research, community service) and the promotion of social responsibility, and the (freedom of expression, and freedom of decision-making) was a weak effect. The results also showed no statistically significant differences for both variables (educational qualification, and years of service) and that there are differences according to the variable of the university in favor of Al-Azhar University. The researchers recommended providing good regulatory environment for the exercise of academic freedom and promote innovation and support for faculty members and urged them to do diverse and creative scientific research and achievement of leadership, and encourage them to participate in conferences, seminars and express their opinions in complete freedom.
Keywords: 330; academic freedom; community responsibility; Faculty members; Palestinian higher educational institutions; Palestinian universities; Gaza Strip